PENGARUH SPRAY GEL EKSTRAK BATANG BAJAKAH TAMPALA (SPATHOLOBUS LITTORALIS HASSK) TERHADAP PENYEMBUHAN LUKA PERINEUM PADA IBU NIFAS - Sindi, Fitriana; Wijayanti, Krisdiana; Ningtyas, Endah Aryati Eko (Poltekkes Kemenkes Bandung, 2024)
Perineal laceration occurred during childbirth, either naturally or through episiotomy. One alternative for perineal wound healing was using a spray gel of Bajakah tampala stem extract, which had anti-inflammatory, antioxidant, and antibacterial benefits that helped accelerate perineal wound healing. The spray technique delivered the preparation directly to the wound without contact with cotton, reducing waste and preventing infection or contamination. This study aimed to determine the effect of Bajakah tampala stem extract spray gel (Spatholobus littoralis Hassk.) on perineal wound healing in postpartum women. The study was conducted at the Eka Setyowati midwife practice and Ngesrep Health Center from January to February 2024. It was a quasi-experiment with a pretest and posttest control group design. Using purposive sampling, 36 respondents were obtained and divided into two groups: the control group, which received dry clean wound care, and the intervention group, which was given Bajakah tampala stem extract spray gel three times a day for seven days with three sprays per application. The perineal wounds were measured using the REEDA scale (Redness, Edema, Ecchymosis, Discharge, Approximation) on the 3rd, 5th, and 7th days. The results showed a decrease in the REEDA score on post-test I (the 5th day), with an average score of 2.78 in the intervention group compared to the control group, which had an average REEDA score of 5.72. The administration of Bajakah tampala stem extract spray gel (Spatholobus littoralis Hassk.) affected perineal wound healing in postpartum women based on the REEDA score.